Sobre a pedagogia em disputa: entre perspectivas e desafios no campo da educação - Silva, Robson Guedes da (Universidade Estadual de Campinas, 2020)
This theoretical essay seeks to establish a reflection around the field of pedagogy, perceiving it as a field in disputes. It tries to think about the challenges that emerge in the field of education today, nourishing itself with discussions about the school institution and its production of subjectivities, as well as the emergence of the field of pedagogy as an effect of production in the modernity of an educational society. It is by tensioning in the present the conservative practices that neoliberalism promotes for the field of education, that this essay, understands theoretical reflection as an important tool of political-pedagogical articulation, enabling new narratives about the field of education